Newborns health in the Danube Region: Environment, biomonitoring, interventions and economic benefits in a large prospective birth cohort study. (March 2016) - Andersen, Zorana J.; Sram, Radim J.; Ščasný, Milan; Gurzau, Eugen S.; Fucic, Aleksandra; Gribaldo, Laura; Rossner, Pavel; Rossnerova, Andrea; Kohlová, Markéta Braun; Máca, Vojtěch; Zvěřinová, Iva; Gajdosova, Dagmar; et al.
Abstract: Background: The EU strategy for the Danube Region addresses numerous challenges including environment, health and socioeconomic disparities. Many old environmental burdens and heavily polluted areas in Europe are located in the Danube Region, consisting of 14 countries, with over 100 million people. Estimating the burden of environmental exposures on early-life health is a growing research area in Europe which has major public health implications, but the data from the Danube Region are largely missing. Aim: This review presents an inventory of current environmental challenges, related early-life health risks, and knowledge gaps in the Danube Region, based on publicly available databases, registers, and literature, as a rationale and incentive for a new integrated project. The review also proposes the concept for the project aiming to characterize in utero exposures to multiple environmental factors and estimate their effect on early-life health, evaluate economic impact, as well as identify interventions with a potential to harness social norms to reduce emissions, exposures and health risks in the Danube Region. Methods: Experts in environmental epidemiology, human biomonitoring and social science in collaboration with clinicians propose to establish a new large multi-center birth cohort of mother-child pairs from Danube countries, measure biomarkers of exposure and health in biological samples at birth, collect centrally measured climate, air and water pollution data, conduct pre- and postnatal surveys on lifestyle, indoor exposures, noise, occupation, socio-economic status, risk-averting behavior, and preferences; and undertake clinical examinations of children at and after birth. Birth cohort will include at least 2000 newborns per site, and a subset of at least 200 mother-child pairs per site for biomonitoring. Novel biomarkers of exposure, susceptibility, and effect will be applied, to gain better mechanistic insight. Effects of multiple environmental exposures on fetal and child growth, respiratory, allergic, immunologic, and neurodevelopmental health outcomes will be estimated. Parent's willingness to pay for reducing health risks in children will be elicited by survey, while values of cost-of-illness will be gathered from literature and national statistics. Effects of risk reducing interventions will be examined. Conclusions: The proposed project would provide novel estimates of the burden of early childhood diseases attributable to environmental exposures and assess health impacts of different intervention scenarios in the Danube Region, in an integrated approach combining human biomonitoring, epidemiological and social science research. Highlights: Many old environmental burdens in Europe are located in the Danube Region. The data on in utero environmental exposures and early-life health are missing. New birth cohort (NEWDANUBE) is proposed integrating human biomonitoring, epidemiological and social science research. The knowledge base for European policy in the area of child and environmental health will be strengthened.